SOCIO-LEGAL AND ETHNIC PEDAGOGICAL ASPECTS OF GENERAL AND SPECIAL FAMILY CODE OF THE RUSSIAN FEDERATION AND THE SHARIA (COMPARATIVE ANALYSIS) - Bika Sh. Aliyeva; Dilshad A. Mehrabova (Вестник Северо-Кавказского федерального университета)
In persisting study is for the first time realized benchmark analysis sharia and household code to Russian Federation. This analysis has shown practicability of the constructive interaction of the moslem right and officially-state. The having Considered condition to families and household education in condition scolded social change, made sure in that that traditional system must not be ruined before basis, ибо system certainly expects simultaneously and successive relationship, intercoupling. Constructive, creative system is not cancealled and does not decay, she is transformed and adapted, adapting to new condition.